2006
DOI: 10.7326/0003-4819-145-11-200612050-00142
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Smoking Cessation Intervention Strategies for Adults and Adults in Special Populations

Abstract: Although self-help strategies alone marginally affect quit rates, individual and combined pharmacotherapies and counseling either alone or in combination can significantly increase cessation. Using effective smoking treatments is strongly encouraged for all populations, especially those with high and heavy rates of smoking, such as psychiatric and substance abuse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 52 publications
1
129
0
5
Order By: Relevance
“…An important component of this service is the delivery of brief cessation advice and referral to "stop smoking clinics" by primary health care providers. However, despite evidence that cessation advice improves quit rates, [12][13][14] studies have shown that primary health care providers are not routinely offering cessation advice during consultations. 15,16 A systematic review published in 2005 suggested that this may be partly due to negative views held by some practitioners about discussing smoking with their patients.…”
Section: -11mentioning
confidence: 99%
“…An important component of this service is the delivery of brief cessation advice and referral to "stop smoking clinics" by primary health care providers. However, despite evidence that cessation advice improves quit rates, [12][13][14] studies have shown that primary health care providers are not routinely offering cessation advice during consultations. 15,16 A systematic review published in 2005 suggested that this may be partly due to negative views held by some practitioners about discussing smoking with their patients.…”
Section: -11mentioning
confidence: 99%
“…Tampoco existen datos referentes a la influencia de este tipo de trastornos en el proceso de abandono del consumo de tabaco, pues la mayoría de las investigaciones se han llevado a cabo en personas dependientes del alcohol, de la cocaína o de opiá-ceos. Los porcentajes de abandono del consumo de tabaco en población que ha padecido o padece un trastorno mental son realmente bajos, pues estos fumadores suelen consumir una mayor cantidad de cigarrillos que la población normal y durante más años (Lawn et al, 2002;Ranney, Melvin, Lux, McClain y Lohr, 2006). En conclusión, es necesario profundizar en la relación entre trastornos de la personalidad y el consumo de tabaco, tanto en la evaluación de dichos trastornos como en el tratamiento de estos fumadores.…”
Section: Discussionunclassified
“…As described in a widespread model, smoking cessation is a process through different motivation stages 12,13 . Motivation is a key element for success, as shown by higher cessation rates for self-referred smokers than for those referred by hospital services 6,14 .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Several types of cessation programs have shown to be effective, for smokers with or without psychiatric disorders [5][6][7] . Tobacco addiction is a chronic disorder 8 and treatment implies multiple quit attempts and relapses, with single interventions showing low success rates 9,10 .…”
Section: Background and Objectivesmentioning
confidence: 99%